Modelo de avaliação do nível de implementação da produção enxuta em cadeias de suprimentos - Reul, Lívia maria Albuquerque (2015)
This work aims to develop a model for assessing the implementation of lean production in supply chains. In order to reach this aim, an analysis of the relevant literature on lean production and lean supply chains was carried out and, based on this literature review, it was possible to identify attributes of lean supply chains that were used to build the conceptual framework and were classified as factors and sub-factors for the assessment model. The Graph Theoretic Approach (GTA) was used as a tool to model the evaluation elements of lean production supply chains, thus the evaluation considers the interrelations between the assessment factors and analyzes the interrelationships between companies that are part of the supply chain. Thus, it brings the required weights for the assessed system, considering that the companies of a supply chain and the assessment factors have mutual relations of influence. Initially, the model evaluates the implementation of the factors individually for each company, and then compose the overall assessment of the supply chain. The model was applied through four case studies from an automotive supply chain, conducted with structured and semi-structured interviews with managers from the logistics department of each company. As a result of the evaluation, it can be concluded that the studied supply chain has an moderate level of implementation of lean production. From the case studies, it was concluded that the proposed model is suitable for their intended purposes, establishing an overall assessment of the implementation of lean production in supply chains.